Bupivacaine Spinal Anesthesia Compared With Etidocaine Epidural Anesthesia for Orthopedic Surgery in Old and Young Patients. Issue 2 (April 1985) - Pitkänen, Mikko T.; Tuominen, Marjatta K.; Rosenberg, Per H.
Abstract : In a randomized study, either bupivacaine 7.5 mg/ml for spinal anesthesia, 3 ml, or etidocaine 15 mg/ml with epinephrine 5 μg/ml for epidural anesthesia, 20 or 25 ml, was administered to twenty older (60-80-year) and twenty younger (20-40-year) patients. In the younger age group, the spread of sensory block was similar in both spinal and epidural groups (T-6 versus T-5). The analgesia during surgery was satisfactory in all patients receiving spinal anesthesia, but in the epidural group, six patients experienced painful sensations during the operation. In the older-age group, the spread of pin-prick analgesia was higher in the epidural group (T-4) than in the spinal one (T-7). Two spinal and four epidural anesthesia patients required additional analgesia during surgery. Spinal anesthesia accelerated motor and tourniquet pain blockade. The mean decrease in systolic arterial pressure during the induction was greater in older patients than in younger ones and was greatest in elderly epidural anesthesia patients (34.5% of preanesthetic value). Backache was the most common postoperative complaint of both spinal (5/20) and epidural (6/20) patients.